Testing of Sewage Sludge Produced in a Model Installation for Water Purification for Antibiotics-Fertilization Products - Zlatareva, E.; Kathijotes, Nicholas; Marinova, Svetla; Zlatareva, E.; Zlatareva, E. (My University, 2008)
Research is carried to establish the effectiveness of the sewage sludge from antibiotic production as an organic fertilizer. Sludge was assessed high to total nitrogen and phosphorus, but with low values of potassium. Data received in a precise short term pot experiment on a grey forest soil showed that different plant species react to the treating with this agent in a different way. The stabilized primary sludge from the I and II bio basins is suitable for cereals under our chemical conditions and agricultural treatment. Increasing the sludge rate proportionally increases the yield of rye-grass and oat. The highest yields are achieved at rates of 40% of the soil weight. In the case of maize the results do not seem satisfactory.
Keywords: Antibiotics; Pot experiments; Sludge; Antibiotics; Pot experiments